2008
DOI: 10.1371/journal.pgen.1000020
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genetic and Chemical Modulators of Zebrafish Mechanosensory Hair Cell Death

Abstract: Inner ear sensory hair cell death is observed in the majority of hearing and balance disorders, affecting the health of more than 600 million people worldwide. While normal aging is the single greatest contributor, exposure to environmental toxins and therapeutic drugs such as aminoglycoside antibiotics and antineoplastic agents are significant contributors. Genetic variation contributes markedly to differences in normal disease progression during aging and in susceptibility to ototoxic agents. Using the later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
234
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 199 publications
(241 citation statements)
references
References 56 publications
7
234
0
Order By: Relevance
“…However, we confirmed these findings using immunocytochemical staining for S100, a calcium binding protein often found in sensory neurons (Abbate et al, 2002;Germanà et al, 2007;Heizmann, 2002). Moreover, confocal imaging showed that the reduced fluorescence of striped bass neuromasts was associated with deformed and sometimes completely missing hair cells following aminoglycoside treatment, similar to zebrafish neuromasts treated with neomycin (Harris et al, 2003;Owens et al, 2007;Owens et al, 2008). Together these results indicate that numerous structural and presumably biochemical changes occur in neuromasts exposed to neomycin and that these changes result in decreased function of the hair cells as reported previously in larval fish (Blaxter and Fuiman, 1989;Mukai, 2006).…”
Section: Discussionsupporting
confidence: 79%
“…However, we confirmed these findings using immunocytochemical staining for S100, a calcium binding protein often found in sensory neurons (Abbate et al, 2002;Germanà et al, 2007;Heizmann, 2002). Moreover, confocal imaging showed that the reduced fluorescence of striped bass neuromasts was associated with deformed and sometimes completely missing hair cells following aminoglycoside treatment, similar to zebrafish neuromasts treated with neomycin (Harris et al, 2003;Owens et al, 2007;Owens et al, 2008). Together these results indicate that numerous structural and presumably biochemical changes occur in neuromasts exposed to neomycin and that these changes result in decreased function of the hair cells as reported previously in larval fish (Blaxter and Fuiman, 1989;Mukai, 2006).…”
Section: Discussionsupporting
confidence: 79%
“…We previously identified both drug treatments and genetic mutations that impede AG entry (42,82,83). Here we show that reducing the total amount of AGs entering the cell also results in a larger relative fraction of AGs being delivered to the lysosomal compartment.…”
Section: Discussionmentioning
confidence: 59%
“…Notably, not all early endocytic routes employ Rab5 (49), including routes that Using this technique, it is straightforward to quantitatively evaluate whether other compounds previously shown to protect HCs from AG exposure affect AG loading. Many such compounds have been identified in LL zebrafish screens (42)(43)(44). Here we show results for benzamil, raloxifene, ractopamine, and dynasore.…”
Section: Resultsmentioning
confidence: 72%
“…ENU mutagenesis and early pressure screens were carried out as described previously (Lister et al, 1999;Owens et al, 2008). Using bulk segregant analysis, the ouchless lesion was linked to chromosome 8, then fine resolution mapping of a total of 1304 individuals narrowed the region to between markers z53446 and z25210.…”
Section: Isolation Of Ouchlessmentioning
confidence: 99%